A pilot study of modified resection for anterior floor of the mouth squamous cell carcinoma without infiltration of the mandible. Issue 3 (March 2019) - Feng, Zhien; Wang, Chong; Li, Bo; Kim, Kyojin; Li, Jinzhong; Mao, Minghui; Qin, Lizheng; Li, Hua; Han, Zhengxue
Abstract: Objective: To explore the application of modified resection compared with traditional segmental resection of the mandible for patients with anterior floor of the mouth and tongue squamous cell carcinoma (SCC) without infiltration of the mandible. Subjects and Methods: This is a retrospective study including 36 eligible patients with anterior floor of the mouth SCC(9 patients received modified mandibulectomy, and 27 patients received segmental mandibulectomy). Results: No patients in the modified mandibulectomy group developed recurrence in the floor of the mouth, and all of the patients survived. Only one patient developed osteoradionecrosis. When the modified mandibulectomy group was compared with the segmental mandibulectomy group, the former exhibited a lower recurrence rate in the floor of the mouth (0.0% vs. 14.8%), less blood loss (516.7 ± 70.7 ml vs. 533.3 ± 93.0 ml), shorter durations of gastric tube placement (11.4 ± 4.5 days vs. 20.7 ± 11.9 days) and tracheostomy (6.9 ± 0.6 days vs. 8.5 ± 1.6 days), a lower postoperative infection rate (11.1% vs. 18.5%), and a shorter postoperative hospital stay (13.7 ± 3.8 days vs. 15.9 ± 5.1 days). Conclusion: This modified mandibulectomy method is safe and feasible and is recommended for further prospective study in a clinical setting.